Enablers and barriers of men with Duchenne muscular dystrophy transitioning from an adult clinic within a pediatric hospital. Issue 1 (January 2017) - Lindsay, Sally; McAdam, Laura; Mahendiran, Tania
Abstract: Background: Young men with Duchenne muscular dystrophy (DMD) live into adulthood and need specialized care. However, services for adults are fragmented. We know little about young men's experiences, their parents, and clinicians who support them as they transition to adult care. Objective: To explore the enablers and barriers of clinicians, young men, and parents as they transition from an adult DMD clinic within a pediatric hospital to an adult health facility. Methods: We conducted semi-structured, in-depth interviews with 16 participants (7 clinicians, 5 parents, 4 youth). We used an open-coding, thematic approach to analyze the data. Results: Clinicians, youth and their parents experienced several enablers and barriers in transitioning to an adult health care center. Clinicians reported that structural factors including leadership and advocacy supported the transition. Clinicians and parents found that the availability and continuity of care both enabled and hindered the transition. Parents and youth conveyed the difficulties of adjusting to the different model of adult care and also accessing resources. All participants described how relational factors (i.e., effective communication and family involvement) enabled the transition. On an individual level, clinicians, parents and youth viewed transition readiness and other life skill supports as an enabler and a barrier to transitioning. All participants reported the difficulties of maintaining mental health for youth with DMD transitioning to adult health care. Conclusions: Clinicians, youth, and parents experienced several enablers and barriers in transitioning to adult health care. Further work is needed to understand the complex transition needs of youth with DMD.